MECHANISMS AND IMPLICATIONS OF ANTIBIOTIC RESISTANCE: A GLOBAL PUBLIC HEALTH CHALLENGE - Mamta Rani; Kuldeep Saharawat (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Antibiotic resistance is a global public health crisis that threatens the effectiveness of treatments for bacterial infections. The rapid rise of multidrug-resistant organisms (MDROs), driven by the overuse and misuse of antibiotics in healthcare, agriculture, and environmental settings, has rendered many infections difficult to treat. This review explores the mechanisms of antibiotic resistance, such as horizontal gene transfer and spontaneous mutations, and examines the role of factors like overprescription, misuse, and environmental contamination in accelerating the spread of resistance. The implications for public health are severe, leading to increased morbidity, mortality, and healthcare costs. Furthermore, antibiotic resistance undermines modern medical procedures, such as surgeries and cancer treatments, which depend on effective antibiotics. Global strategies to combat antibiotic resistance include promoting antibiotic stewardship, improving infection control, and encouraging responsible antibiotic use in agriculture. Alongside policy initiatives, scientific innovation is crucial, with new antibiotics and alternative therapies—such as antimicrobial peptides, bacteriophage therapy, and CRISPR-based interventions—offering potential solutions. Coordinated international efforts and continued investment in research are essential to mitigate the impact of antibiotic resistance and protect global health.